COTTAPP: An Online University Timetable Application based on a Goal Programming Model - Dursun, Tugce; Su, Yasemin; Cosgun, Rana; Durak, Ayse Sevde; Yet, Barbaros (International Journal of Intelligent Systems and Applications in Engineering, 2017)
Preparing university course timetables is a challenging task as many constraints and requirements from the university and lecturers must be satisfied without overlapping courses for different student groups. Although many mathematical optimization models have been proposed to automate this task, a wider use of these models have been limited as deep technical understanding of mathematical and computer programming are required in order to use and implement them. This paper proposes a simple and flexible course timetabling application that is based on a weighted binary goal programming model with a powerful solver. Our application enables the users to modify and run this model by using a simple web and spreadsheet interface. Consequently, the model does not require deep technical understanding of the underlying models from its users even though it is based on a complex mathematical model. The web application and the underlying optimization model is illustrated by using a case study of an undergraduate program of industrial engineering.Â Â